2017
DOI: 10.1111/apm.12752
|View full text |Cite
|
Sign up to set email alerts
|

Primary antibiotic resistance of Helicobacter pylori strains among adults and children in a tertiary referral centre in Lithuania

Abstract: The study evaluated primary antibiotic resistance of Helicobacter pylori within the period 2013-2015 and trends of antibiotic consumption over the last decade in Lithuania; 242 adults and 55 children were included in the study. E-tests were performed for amoxicillin, metronidazole, clarithromycin, ciprofloxacin, rifampicin and tetracycline. The presence of H. pylori and clarithromycin resistance was additionally tested by PCR. Helicobacter pylori culture was positive in 67 of 242 (28%) adult and in 12 of 55 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…Analogous findings were observed by Shu et al who showed a significant increase in CH resistance from 11% in 2012 to 26% in 2014 [ 21 ]. Similar increasing trends in CH resistance in children was observed by other authors from Europe and Asia [ 22 , 23 , 24 ]. The single resistance of H. pylori strains isolated from children to MET in our region remains stable, but high (from 28.6% in the period from 2008–2012 to current 31%), similar to other European countries (15–30%), but it is much higher in Iran (60%) and in China (68%) [ 13 , 20 , 21 , 22 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Analogous findings were observed by Shu et al who showed a significant increase in CH resistance from 11% in 2012 to 26% in 2014 [ 21 ]. Similar increasing trends in CH resistance in children was observed by other authors from Europe and Asia [ 22 , 23 , 24 ]. The single resistance of H. pylori strains isolated from children to MET in our region remains stable, but high (from 28.6% in the period from 2008–2012 to current 31%), similar to other European countries (15–30%), but it is much higher in Iran (60%) and in China (68%) [ 13 , 20 , 21 , 22 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Among Israeli children and adolescents, compared with patients naïve to anti- H. pylori treatment, patients who were previously treated for H. pylori had a threefold higher resistance rate for clarithromycin and a twofold higher resistance rate for metronidazole [12]. The resistance rates for metronidazole and ciprofloxacin were significantly higher in adults than in children [13]. In addition, the antibiotic resistance rate is also associated with age, gender, the type of gastric disease, and the location of the patient [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Current therapies, such as triple therapies, quintuple therapies and high-dose dual therapies, are based on using bismuth, proton pump inhibitors and antibiotics. These therapies are facing challenge of increasing resistance to the first-line antibiotics like clarithromycin, metronidazole and levofloxacin 3 5 . Vaccination has been proposed as the most promising strategy for control of this infection, but so far no commercial vaccine is available 6 .…”
Section: Introductionmentioning
confidence: 99%